Community Participation in Flash Flood Disaster Risk Reduction Efforts in Doyo Baru Village, Waibu District, Jayapura Regency - Lazarus Ramandei (Journal of Technology and Engineering, 2026)
Doyo Baru Village is one of the villages in Waibu District, Jayapura Regency. Doyo Baru Village is one of the villages affected by the 2019 flash flood disaster. Flash Flood Disaster is an event or series of events that result in casualties, property losses, environmental damage, facilities and infrastructure as well as disruption to the order of human life and livelihood. This research aims to: 1. Knowing the impact of flash floods in Doyo Baru Village, Waibu District. 2. Knowing community participation in reducing the risk of flash floods in Doyo Baru Village, Waibu District. The results of research on community participation in flood disaster risk reduction efforts in Doyo Baru Village, Waibu District, Jayapura Regency are considered not running optimally in accordance with the program. Based on the results of the questionnaire conducted by the author, 37% of the people who participated in the counseling and 63% who did not. It can be concluded that the government has tried to provide counseling on flood disaster risk, but some people in Doyo Baru Village did not all participate. Based on the results of distributing questionnaires to the community regarding the impact of flash floods, people who answered yes with a percentage of 91% of community respondents who answered no with a percentage of 9%. It can be seen that Kampung Doyo Baru on the impact of the disaster that occurred had a major impact on the people affected by the floods in Kampung Doyo Baru.